GESTÃO ESTRATÉGICA E LIDERANÇA NO TERCEIRO SETOR: UM ESTUDO DE CASO EM ORGANIZAÇÕES NÃO GOVERNAMENTAIS - Soares, Carlos Alberto Lidizia (2004)
The proposal of this study is to contribute to make the management practices related to strategic planning of organizations better, mainly for the called Non-Governmental Organizations - NGO, where management practices are identified and leadership performance are systematized. Using a multiple case study and two criteria of excellency from PQN - 2004, Foundation for Quality National Price - Leadership and Strategy & Plans - and TOP Price Enterprise of QP-Rio, three organizations will have theirs management practices analyzed. As a result of the research, was concluded that the NGO develop management practices seeking to keep the partnership and the confident is increasing in those organizations, which transformation can be translated by the evidences shown in the research, checked by the constant concern of their leadership on quality, transparency and relationship with the stakeholders